Managing semantic evolution in databases: from theory to implementation - Nepomuceno, Pedro Ivo Siqueira; Braghetto, Kelly Rosa (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
Long-lived databases undergo continuous semantic change: categories are renamed, standards revised, boundaries merged or split. Unlike schema evolution, these value-level shifts lack principled solutions, leaving users to reconcile discrepancies by hand. This thesis formalizes semantic evolution as time-stamped operations over an interval-based storage model, and derives two approaches that answer queries transparently: query rewriting and data preprocessing. Implemented in MellowDB, a MongoDB-based Python middleware, both proved production-ready on 30 years of Brazilian mortality records: preprocessing excels in read-oriented scenarios, whereas query rewriting becomes preferable as writes dominate.